1997
DOI: 10.1080/03079459708419191
|View full text |Cite
|
Sign up to set email alerts
|

The prophylactic effect of vitamin C supplementation on broiler ascites incidence and plasma thyroid hormone concentration

Abstract: In a two-factorial experiment, 420 1-day-old male commercial broiler chickens were randomly divided and fed a basal diet with or without vitamin C (500 parts/10(6)). Half of the birds within each group receiving the same kind of feed were fed a T(3 )supplemented diet from day 1, in order to increase the ascites incidence. Weekly body weight and feed intake were measured. Venous blood samples were taken from 10 birds per group weekly from day 14 on, for haematocrit measurements, blood gas analysis, measurement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(14 citation statements)
references
References 24 publications
2
11
0
Order By: Relevance
“…The results of the present study demonstrate that the administration of AA just before journey start is beneficial in terms of reducing the stressful effect of being transported during hot and humid weather. In addition, they confirm previous findings that AA increases body resistance to environmental stress [12,22,23], by altering the hormones or factors responsible for a shift in the homeostatic mechanism during stressful conditions [18], and by so doing restores the organism's excitability.…”
Section: Discussionsupporting
confidence: 87%
“…The results of the present study demonstrate that the administration of AA just before journey start is beneficial in terms of reducing the stressful effect of being transported during hot and humid weather. In addition, they confirm previous findings that AA increases body resistance to environmental stress [12,22,23], by altering the hormones or factors responsible for a shift in the homeostatic mechanism during stressful conditions [18], and by so doing restores the organism's excitability.…”
Section: Discussionsupporting
confidence: 87%
“…(2005) reported similar results. However, Ladmakhi et al. (1997) showed that AA up to 500 ppm had no effect on F:G of broilers maintained in the cyclic temperature (24–35 °C) during 28–42 days of age.…”
Section: Discussionmentioning
confidence: 94%
“…Nevertheless, Packed Cell Volume, weight gain and feed efficiency were not affected by the treatment (Table 1). In addition to the suggestions that vitamin C may exert positive effects on alleviating ascites because it depresses the oxygen-derived free radical status (Ladmakhi et al, 1997), the results presented in Table 1 show that vitamin C markedly reduced the muscularization of the pulmonary arterioles as indicated by the lower number of thick-walled peripheral vessels (TWPV). Thus, it may reduce the resistance to blood flow that is seen in pulmonary vessels of broilers.…”
Section: Nutritional Controlmentioning
confidence: 92%